Has Foreign Aid Been Effective in the Water Supply and Sanitation Sector? Evidence from Panel Data. (September 2016) - Gopalan, Sasidaran; Rajan, Ramkishen S.
Highlights: Aid has a positive effect on improved access to Water Supply and Sanitation (WSS). We also find strong evidence of non-linearities between aid flows and outcomes. Aid disbursements are effective only in lower-middle-income-countries. Aid to WSS tends to have 'diminishing returns'. Aid disbursements enhance access to WSS in rural more than urban areas. Summary: A voluminous academic literature exists on the effectiveness of foreign aid in general. However, relatively less work has been done on the impact of sector-specific foreign aid. This paper focuses on the impact of aid disbursements on outcomes in the Water Supply and Sanitation (WSS) Sector. Despite the considerable increase in aid flows to the WSS sector over the last few years, it is only recently that the literature has started to focus on assessing aid effectiveness in this sector. We contribute to the growing interest in sector-specific aid effectiveness literature by conducting an empirical analysis for a large panel of countries to assess the effectiveness of aid disbursements on improved access to WSS facilities. Our empirical results suggest that aid disbursements produce a strong, positive, and significant effect on improved access to WSS, and our results are robust to multiple specifications and estimation procedures. We also find strong evidence of non-linearities governing the relationship between aid flows and outcomes, in that aid disbursements are effective only in lower middle-income-countries rather than low-income-countries or upper middle-income countries. These results tend to suggest that a country needs to meet a certain development or income threshold before aid can prove to be effective and that aid flows tend to have diminishing returns. Finally, we also find that aid disbursements produce favorable effects in enhancing access to WSS facilities in rural as opposed to urban areas.